Development of E-Modules Assisted By Augmented Reality on Alternative Energy Material - Izdihar, Diva; Liliawati, Winny; Danawan, Agus; Sasmita, Dedi (Program Studi Pendidikan Fisika, Universitas PGRI Semarang, 2024)
The ability to interpret, use, and create visual media to improve processes, decision-making, communication, and learning is known as visual literacy. Learning that trains visual literacy is needed to prepare students' abilities in the future. The purpose of this research is to develop and identify the feasibility of Augmented Reality-assisted E-Module on alternative energy materials in training literacy. The research method used is Research and Development (R&D) with the ADDIE development model. This research only carried out three stages of the ADDIE development model, namely: Analysis, Design, and Development. To identify the feasibility of the E-Module, validation and testing are carried out. Validation was carried out by 3 physics lecturers and 2 physics teachers with a result of 91% (very feasible category). Then in the rumpang test, it showed a readability level of 96.2% (independent category). So it can be concluded that the E-Module is easy to understand and can be used independently by each student.